Los condicionamientos pragmáticos del uso de los deícticos de tiempo en español - Brzozowska-Zburzyńska, Beata (Studia Romanica Posnaniensia, 2021)
The objective of this study is to reflect on the Spanish time expressions that function as deictic elements. Deixis is a phenomenon strictly related to aspects of a pragmatic nature since it depends on the situational context in which the participants of the communicative act are. We want to search, discover and describe the pragmatic conditioning that determines the appearance and operation of this type of element in Spanish. Our idea is to demonstrate that in time deictic expressions the semantic content is not enough for speakers to use these expressions properly. It is necessary to resort to information that exceeds the level of meaning and find guidelines for the good interpretation of the expression in the situational and personal context. The group of time deictics is not heterogeneous from the formal point of view. It includes simple elements (for example, adverbs) and more or less complex elements (noun and prepositional phrases). We will focus on this second group and, above all, on the nominal constructions that include determinants and temporal adjectives since in this type of structure each constituent element performs a different semantic-pragmatic function and only the combination of these allows us to discover the definitive value of the set.